1974
DOI: 10.1111/j.1365-2133.1974.tb06411.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical antibiotics in pyodermas

Abstract: SUMMARY The value of topical antibiotics in the treatment of pyodermas was reassessed. In a double‐blind study, the efficacy of 0.1% gentamicin cream was tested. There was no significant statistical difference in the degree of improvement between the group of patients that received the gentamicin cream and those treated with a placebo. The response obtained was thought to be due to washing and removal of crusts. Hence, it is considered advisable to abstain from the use of topical antibiotics in pyodermas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…By using the same technique, the relative potencies of 0.1% betamethasone valerate, 0.025% fluocinolone acetonide, and 0.1% triamcinolone acetonide creams were evaluated and found to have practically the same potency (123). These results correlated well with double-blind clinical studies.…”
Section: Intensity Of Inflammatory Stimulus Applied Therementioning
confidence: 53%
“…By using the same technique, the relative potencies of 0.1% betamethasone valerate, 0.025% fluocinolone acetonide, and 0.1% triamcinolone acetonide creams were evaluated and found to have practically the same potency (123). These results correlated well with double-blind clinical studies.…”
Section: Intensity Of Inflammatory Stimulus Applied Therementioning
confidence: 53%
“…The final selection of publications included 4 placebo-controlled uSSTI trials (35)(36)(37)(38), 12 linezolid trials (39-50), 3 ceftaroline trials (51-53), 1 retrospective ceftaroline secondary analysis (54), and 2 nonantibacterial treatment trials of UV light for erysipelas (23,24) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The four trials as proxy for placebo included 234 subjects with a range of uncomplicated infections reported as impetigo, folliculitis, SITL, and pyoderma (Table 1). Publication dates were from 1974 to 2013, three of the trials enrolled a subset of subjects Ͻ18 years of age, and one publication required certified translation from French to English (35)(36)(37)(38). Each trial reported a TOC clinical treatment response; none reported an early clinical treatment response.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations